Case of practical diagnosis of Morton’s neuroma - G. P. Volkov; M. V. Babaev (Медицинский вестник Юга России, 2019)
A clinical case of Morton’s neuroma in a 46-year-old patient is presented. The article presents in detail the technology of ultrasound examination of the foot in the considered pathology. Describes the characteristics of clinical manifestations and ultrasound semiotics of lesions of the interdigital nerve. It is shown that currently ultrasound is the optimal and highly informative method of radiation diagnosis in the recognition of Morton’s neuroma.